2020
DOI: 10.3390/jcm9082470
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Outcome of Epiretinal Membrane Surgery in Patients with Internal Limiting Membrane Dehiscence

Abstract: Purpose: To identify the effect of internal limiting membrane (ILM) dehiscence on surgical outcomes in eyes that have undergone epiretinal membrane (ERM) removal. Methods: Consecutive eyes with performed vitrectomy for ERM removal were included. Subjects were divided into two groups: patients with ILM dehiscence (group 1) and without ILM dehiscence (group 2). The best-corrected visual acuity (BCVA) and retinal layer thickness before and after surgery were compared between the two groups. Results: A total of 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Actually, the reduction in IRL was associated with BCVA improvement in our study. Such a reduction may be one of the healing processes after sealing of the FTMH, similar to the process after surgery for the epiretinal membrane, as opposed to contributing to microvasculature impairment 11 , 22 . Further longitudinal studies for changes in macular microvasculature using optical coherence tomography angiography are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the reduction in IRL was associated with BCVA improvement in our study. Such a reduction may be one of the healing processes after sealing of the FTMH, similar to the process after surgery for the epiretinal membrane, as opposed to contributing to microvasculature impairment 11 , 22 . Further longitudinal studies for changes in macular microvasculature using optical coherence tomography angiography are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational study adhered to the tenets of the Declaration of Helsinki and was approved by the Institutional Review Board of Konyang University Hospital, Daejeon, Korea, and informed consent was obtained from all of the patients. We obtained detailed histories and best-corrected visual acuity (BCVA), intraocular pressure, spherical equivalent, and axial length 11 . All patients underwent 25-gauge PPV with ILM peeling using indocyanine green, and fluid-gas exchange using C 3 F 8 or SF 6 with face down posturing.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Internal limiting membrane dehiscence is not associated with preoperative visual acuity, but with poor final postoperative visual acuity. 11,19 This study showed that preoperative BCVA was worse in cases with RNFL schisis and postoperative BCVA was worse, and the degree of improvement in BCVA was lower in cases with macular fluorescein leakage. Postoperative BCVA was worse in patients with both macular fluorescein leakage and RNFL schisis than in those without both factors (Figure 3).…”
Section: Discussionmentioning
confidence: 85%
“…12,13 Internal limiting membrane dehiscence is not associated with preoperative visual acuity, but with poor final postoperative visual acuity. 11,19…”
Section: Discussionmentioning
confidence: 99%
“…The authors would like to correct the keyword ‘bare RNLF’ to ‘RNFL schisis’ in their prior publication [ 1 ]. The word ‘bare RNFL’ was first used in a previous study published 2 months before these authors’ paper [ 2 ].…”
mentioning
confidence: 99%